PENGUATAN PERAN UNIT PENGUMPUL ZAKAT (UPZ) BERBASIS MASJID DI KABUPATEN GOWA, SULAWESI SELATAN - muhammad shuhufi; Fatmawati (ISTIQRA: Jurnal Hasil Penelitian, 2022)
The Mosque-based Amil Zakat Institution (LAZ) has the potential to develop zakat in Gowa Regency, the research uses the community-based research (CBR) method, which includes efforts to create solutions to problems and opportunities for developing zakat empowerment in the Regency, especially those related to strengthening the Zakat Collection Unit Mosque based. The results of the research show that the practice of implementing the functions and roles of UPZs is already running at the mosque level in the Regency, but it is not yet running following statutory regulations and UPZ institutions have not yet been formed in the majority of Mosques in Gowa Regency, so the strengthening program carried out by researchers will be on the agenda and Baznas work program to involve religious counselors